Distinct moieties underlie biphasic H+ gating of connexin43 channels, producing a pH optimum for intercellular communication - Garciarena, C; Malik, A; Swietach, P; Moreno, A; Vaughan-Jones, R (Federation of American Society of Experimental Biology, 2018)
Most mammalian cells can intercommunicate via connexin-assembled, gap-junctional channels. To regulate signal transmission, connexin (Cx) channel permeability must respond dynamically to physiological and pathophysiological stimuli. One key stimulus is intracellular pH (pHi), which is modulated by a tissue’s metabolic and perfusion status. Our understanding of the molecular mechanism of H+ gating of Cx43 channels—the major isoform in the heart and brain—is incomplete. To interrogate the effects of acidic and alkaline pHi on Cx43 channels, we combined voltage-clamp electrophysiology with pHi imaging and photolytic H+ uncaging, performed over a range of pHi values. We demonstrate that Cx43 channels expressed in HeLa or N2a cell pairs are gated biphasically by pHi via a process that consists of activation by H+ ions at alkaline pHi and inhibition at more acidic pHi. For Cx43 channel–mediated solute/ion transmission, the ensemble of these effects produces a pHi optimum, near resting pHi. By using Cx43 mutants, we demonstrate that alkaline gating involves cysteine residues of the C terminus and is independent of motifs previously implicated in acidic gating. Thus, we present a molecular mechanism by which cytoplasmic acid–base chemistry fine tunes intercellular communication and establishes conditions for the optimal transmission of solutes and signals in tissues, such as the heart and brain.—Garciarena, C. D., Malik, A., Swietach, P., Moreno, A. P., Vaughan-Jones, R. D. Distinct moieties underlie biphasic H+ gating of connexin43 channels, producing a pH optimum for intercellular communication.